DESIGN FACTORIAL ANALYSIS: IDENTIFYING THE INTERACTIONS WORKPLACE MINDFULNESS AND INDIVIDUAL FACTORS IN CONTROLLING AFFECTIVE COMMITMENT - Riani, Dini; Sopiansah, Veri Aryanto (Jurnal Riset Bisnis dan Manajemen, 2023)
This research is motivated by changes in organizational culture, high work pressure, shifts in individual values, and attention to the workplace which are common causes of decreased affective commitment. By paying attention to these factors and implementing appropriate steps, organizations can increase employee affective commitment. This study uses a quantitative perspective with the factorial method for problem solving, taking into account the interaction of each factor in the variables used. Research participants used FKIP Pasundan University graduates who worked for at least two years unless they were self-employed. The results showed that affective commitment can occur due to the interaction between workplace mindfulness and individual factors, this reflects the level of satisfaction, loyalty, and emotional attachment that employees feel towards their organization. Circumstances where employees are satisfied with their work and the organization provides sufficient attention will create stronger emotional bonds and higher commitment to the organization.